Endoscopic-assisted Distal Biceps Footprint Repair. Issue 2 (June 2015) - Phadnis, Joideep; Bain, Gregory
<x xml:space="preserve">Abstract</x> Distal biceps tendon ruptures have been treated successfully with a variety of techniques; however, no current technique is able to restore the biceps to its native footprint on the ulnar surface of the radial tuberosity. We describe a technique, using an endobutton that better recreates the anatomic distal biceps footprint. This is likely to better restore absoloute and repetitive supination strength, which is not reliably achieved with current techniques.